Nilai-Nilai Etika Bisnis Islam dalam Praktik UMKM Dendeng Pucuk Ubi Wak Idah - Purwandari, Elce; Mukmin , Agus (AMAL: Jurnal Ekonomi Syariah, 2025)
This study examines the application of Islamic business ethics values in the operations of the MSME Dendeng Pucuk Ubi Wak Idah, and their influence on the sustainability and reputation of the business from the perspective of customers and the surrounding community. The main problem addressed is how Islamic ethical values are implemented in business practices and how these values foster customer trust and loyalty. The research employs a qualitative approach, using in-depth interviews with key informants, including the business owner, employees, customers, suppliers, religious leaders, and neighbors. Findings reveal that honesty, trustworthiness, responsibility, and fairness are the fundamental principles consistently upheld in the business. These values not only build a positive reputation and harmonious relationships with stakeholders but also strengthen the business’s sustainability through customer trust and community support. This study contrIbutes to MSME management theory by incorporating spiritual and social relationship dimensions as key factors for success. In conclusion, the comprehensive internalization of Islamic business ethics is crucial in maintaining and developing MSMEs. Practical recommendations are offered for MSME practitioners to integrate these values to enhance trust and competitiveness, and for future research to expand studies to other MSME sectors.